A Double Inverted F-Shape Patch Antenna for Dual-Band Operation. (27th April 2014) - Islam, M. M.; Faruque, M. R. I.; Hueyshin, W.; Mandeep, J. S.; Islam, T.
Abstract : A double inverted F-shape patch antenna is presented for dual-band operation. The proposed antenna is comprised of circular and rectangular slots on a printed circuit board of 40 mm × 40 mm × 1.6 mm with a 50 Ω microstrip transmission line. Commercially available high frequency structural simulator (HFSS) based on the finite element method (FEM) has been adopted in this investigation. It has a measured impedance bandwidths (2 : 1 VSWR) of 18.53% on the lower band and 7.8% on the upper band, respectively. It has achieved stable radiation efficiencies of 79.76% and 80.36% with average gains of 7.82 dBi and 5.66 dBi in the operating frequency bands. Moreover, numerical simulations have been indicated as an important uniformity with measured results.